Intravenous Bone Marrow Mononuclear Cells for Acute Ischemic Stroke: Safety, Feasibility, and Effect Size from a Phase I Clinical Trial - Vahidy, Farhaan S.; Haque, Muhammad E.; Rahbar, Mohammad H.; Zhu, Hongjian; Rowan, Paul; Aisiku, Imoigele P.; Lee, Dean A.; Juneja, Harinder S.; Alderman, Susan; Barreto, Andrew D.; Suarez, Jose I.; Bambhroliya, Arvind; et al. (Stem cells (Dayton, Ohio), 2019)
Cellular therapy is a promising investigational modality to enhance poststroke recovery. We conducted a single‐arm, phase I clinical trial to determine the safety and feasibility of intravenous (IV) administration of autologous bone marrow mononuclear cells (MNCs) after acute ischemic stroke (AIS). Patients with moderate severity of AIS underwent bone marrow harvest followed by IV reinfusion of MNCs within 24–72 hours of onset. A target dose of 10 million cells per kilogram was chosen based on preclinical data. Patients were followed up daily during hospitalization and at 1, 3, 6, 12, and 24 months for incidence of adverse events using laboratory, clinical (12 months), and radiological (24 months) parameters. The trial was powered to detect severe adverse events (SAEs) with incidences of at least 10% and planned to enroll 30 patients. Primary outcomes were study‐related SAEs and the proportion of patients successfully completing study intervention. A propensity score‐based matched control group was used for the estimation of effect size (ES) for day‐90 modified Rankin score (mRS). There were no study‐related SAEs and, based on a futility analysis, enrolment was stopped after 25 patients. All patients successfully completed study intervention and most received the target dose. Secondary analysis estimated the ES to be a reduction of 1 point (95% confidence interval: 0.33–1.67) in median day‐90 mRS for treated patients as compared with the matched control group. Bone marrow harvest and infusion of MNCs is safe and feasible in patients with AIS. The estimated ES is helpful in designing future randomized controlled trials. Stem Cells 2019;37:1481–1491 Diffusion tensor tractography using serial multimodel magnetic resonance imaging contrast in a representation patient who received autologous bone marrow‐derived mononuclear cells after acute ischemic stroke.